Komparace vývoje nezaměstnanosti v České republice a na Slovensku - Černohorská, Liběna (Univerzita Pardubice, 2006)
This article deals with a comparison of a trend of unemployment together with factors, which caused different trend of unemployment in Czech Republic and in Slovakia. The state policy of unemployment is executed in this two countries. Since 2004 are implemented new tools of the active policy of unemployment, which serve to decrease unemployment and deepen cooperation with the job applicants.
Keywords: Nezaměstnanost; vývoj nezaměstnanosti; analýza vývoje; politika zaměstnanosti; Česká Republika; Slovensko; komparace